Silica weight percent from IODP Site 323-U1340 - Kimberly deLong; Terrence Blackburn; Beth Caissie; Jason A Addison; Zuzanna N Stroynowski; Maria Reimi Sipala; Franco Marcantonio; Ana Christina Ravelo (PANGAEA, 2025)
The Bølling-Allerød deglacial event is marked by high diatom productivity and opal deposition throughout the subarctic Pacific. To investigate the cause of this event, we quantified several productivity-related sedimentary parameters that reflect the near-surface biogeochemistry from the Integrated Ocean Drilling Program (IODP) Site 323-U1340 in the Bering Sea. Bulk sediment weight% nitrogen (wt% Si) was measured on an Elemental Analyzer in the Stable Isotopes Laboratory at the University of California Santa Cruz using 80 mg of freeze-dried, pulverized, homogenized sediment samples.